THE EFFECT OF SNOWBALL THROWING TECHNIQUE IN TEACHING READING COMPREHENSION AT GRADE TENTH STUDENTS OF SMA SWASTA KAMPUS NOMMENSEN PEMATANG SIANTAR - Sanggam Siahaan; Juni Mariana Simanungkalit; Melda Veby Ristella Munthe (KOLONI, 2022)
This study focuses on the technique of throwing snowballs in teaching reading comprehension at grade tenth students of SMA Swasta Kampus Nommensen Pematangsiantar in narrative text. therewere problems which related on this research The problem of the students Students had low in reading comprehension,The students not familiar with the vocabulary in the text, and Students did not understand how to find out the main idea in the reading narrative text. whether this technique can improve the reading comprehension ability of he grade tenth at SMA Swasta kampus Nommensen Pematangsiantar campus. The snowball throwing technique can be used as a teaching tool for students to learn in teaching reading comprehension. Research Problem Formulation is, is There a More Significant Effect of Snowball Throwing Technique on Reading Comprehension at grade tenth Students of SMA Swasta Kampus Nommensen Pematangsiantar in Narrative Text? This study uses an experimental design, meaning that there are certain experiments that are applied to the population or sample. And the population of this study is four classes, namely students in the second year of 2022/2023 of SMA Swasta Kampus Nommensen Pematangsiantar. and the sample for the The researcher used a proposive sampling. There were 25 students in each classroom. The control group using (textbook) while the experimental group was taught using snowball throwing technique. In this reseaarch, Data analysis revealed that the post-test mean score for the experimental group was 80, whereas the control group's score was 59,68. The effect of applying snowball throwing technique more significants than the effect of texbook to the ability of grade tenth students of SMA Swasta Kampus Nommensen Pematangsiantar in narrative tex. This can be proven from the t-count of 2.21 and the t-table value is 2.011 at alphe 0.05 and df= 48 ( Nx + Ny -2 = 25+25-2 = 48 ). The t-test value is higher than the t-table value (t-test > t-table). Therefore, the alternative hypothesis (Ha) accepted and the null hypothesis (Ho) rejected. Keywords: Snowball throwing technique, reading comprehension, narrative Text